Estudio del confortt por temperatura y su incidencia en el trastorno sistémico por calor en los trabajadores de la tuneladora 1 del frente de conducción de la empresa Sinohydro Conporation en el proyecto hidroeléctrico Coca Codo Sinclair. Diseño de un programa de control de prevención de riesgos por calor. - Yachimba Guachi, Angel Eduardo (2014)
This investigation work was made a confort study per temperature and incidence of systemic disorders of workers on the tunneling machine 1 of the front driving company Sinohydro Corporation on the Coca Codo Sinclair hydroelectric project, and a program of risks was developed by heat; to make this research began by identifying workers using statistical data and records of the Department of Occupational Health Company of the company and then make measurements on the environment of the work with certified and calibrated machines (temperature measurer WBGT and the anemometer); and personal facts of the work population on this research. To deepen the research a study was made in order of each job position and the application of NTP 323 tables: determine of the energy metabolism; to determine the metabolic consume in the workers, and the NTP 74: Fanger thermal comfort-Method for evaluation, to determine the percentage of dissatisfied workers by the temperature. The hypothesis test in this research is: hot environmental physical parameters for comfort for temperature affect the systemic disorder by the heat of the workers on the tunneling machine 1 the front driving company Sinohydro Corporation on the Coca Codo Sinclair, to propose a Program of Risk Prevention because of heat, this research work product determined the measurements of control to hot places and of the of systemic disorders in workers of the TBM.